2015
DOI: 10.1016/j.carbon.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Do CVD grown graphene films have antibacterial activity on metallic substrates?

Abstract: Accurate assessment of the antibacterial activity of graphene requires consideration of both the graphene fabrication method and, for supported films, the properties of the substrate.Large-area graphene films produced by chemical vapor deposition were grown directly on copper substrates or transferred on a gold substrate and their effect on the viability and proliferation of the Gram-positive bacteria Staphylococcus aureus and the Gram-negative bacteria Escherichia coli were assessed. The viability and the pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…However, in a later report, Dellieu et al. ruled out the electron‐transfer model as a mechanism to explain the presumed antibacterial activity of CVD graphene films . They found that graphene films that entirely covered Cu or Au substrates showed negligible antibacterial activity against S. aureus and E. coli , whereas a Cu substrate with a partial coverage of graphene slightly inhibited the growth of bacteria and bare Cu completely suppressed the growth of these microorganisms, which is ascribed to the release of bactericidal Cu 2+ .…”
Section: Antimicrobial Activity Of Gmsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a later report, Dellieu et al. ruled out the electron‐transfer model as a mechanism to explain the presumed antibacterial activity of CVD graphene films . They found that graphene films that entirely covered Cu or Au substrates showed negligible antibacterial activity against S. aureus and E. coli , whereas a Cu substrate with a partial coverage of graphene slightly inhibited the growth of bacteria and bare Cu completely suppressed the growth of these microorganisms, which is ascribed to the release of bactericidal Cu 2+ .…”
Section: Antimicrobial Activity Of Gmsmentioning
confidence: 99%
“…However, in al ater report, Dellieu et al ruled out the electron-transfer modela samechanism to explain the presumed antibacterial activity of CVD graphene films. [47] They found that graphene films that entirely covered Cu or Au substrates showedn egligible antibacterial activity against S. aureus and E. coli,w hereas aC us ubstrate with ap artial coverage of graphene slightly inhibited the growth of bacteria and bare Cu completely suppressed the growth of these microorganisms, which is ascribed to the release of bactericidal Cu 2 + .I na ddition to graphene-film-coateds urfaces, the antibacterialp erformance of GO film-coateds ubstrates hasa lso been investigated. For example, in av ery recent report, Panda et al demonstrated that electron transfer affects the antibacterial properties of shellac-derived GO films on different substrates.…”
Section: Induction Of Oxidative Stressmentioning
confidence: 99%
“…[57][58][59] Several research reports are available, documenting the possible mechanisms for growth inhibition of bacterial strains by carbon nano tubes, fullerenes, and graphene family nanostructures. [60][61][62][63][64][65] But the exact mechanism explaining the loss of bacterial integrity is still a researchable topic.…”
Section: F Antibacterial Studymentioning
confidence: 99%
“…The antibacterial activity of graphene-family materials and their hybrid materials have been widely studied in recent year [ 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Different antibacterial organic compounds and polymers were used to functionalize graphene-family materials in order to enhance the antibacterial activity of the resulting composites.…”
Section: Introductionmentioning
confidence: 99%